Elderly-onset pulmonary sarcoidosis: A radiological approach to diagnosis - Doğan, Sevtap; Öztürk, Onural; Aydoğan Diş, Sevil; Argun Barış, Serap; Doğan, Nurettin Özgür (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2023)
Background and aim: The aim was to compare the radiological and clinical characteristics of sarcoidosis between elderly and non-elderly patients.Methods: This retrospective observational study was carried out in patients with sarcoidosis. Elderly-onset sarcoidosis was defined as sarcoidosis diagnosed in patients ≥65 years-old. Patients were stratified by age (≥65 years versus